Composite fabric and clothes made of composite fabric
By using a composite hot melt adhesive with a double-layer film structure in UV-resistant clothing fabrics, the components are adjusted to form cracks, and sweat diversion problem is solved, achieving efficient sweat management and clothing comfort.
Patent Information
- Application Number
- CN202510086035.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-20
AI Technical Summary
When existing UV-resistant clothing fabrics sweat for a short period of time in summer, sweat will block the pores of the fitting membrane layer, causing sweat to not effectively divert flow, causing discomfort in dressing.
The composite hot melt adhesive with a double-layer film structure is used to adjust the components of each layer of hot melt adhesive, so that the composite hot melt adhesive can produce cracks on the side of the bonding waterproof fabric, thereby achieving sweat flow diversion.
It achieves the maintenance of waterproof performance, moisture permeability, water pressure resistance and ultraviolet barrier properties, and solves the problem of sweat diversion and improves the comfort of clothing.
Smart Images

Figure CN119820971A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fabric materials, and in particular to a composite fabric and clothing thereof. Background Art
[0002] CN117757407A discloses a fabric, including a waterproof fabric on the surface, a hydrophilic fabric on the bottom layer and a bonding film layer between the two, wherein the bonding film layer is a hot melt adhesive for bonding anti-ultraviolet clothing fabric; the hot melt adhesive for bonding anti-ultraviolet clothing fabric is composed of 70-80 parts of thermoplastic polyurethane elastomer, 20-30 parts of polyether polyol-modified silk protein, and 10-15 parts of nano silicon dioxide, and the waterproof performance is 4 levels before washing and 3 levels after washing, and the moisture permeability is 8000g / m 2 The above, water pressure resistance of more than 5000mmH2O, and excellent UV blocking performance. In actual use, the jacket made of this fabric is found to have the problem that the water conduction performance cannot meet the application in special circumstances. For example, in summer, when a large amount of sweat is produced in a short period of time, the sweat will block the pores of the laminated film layer, and the hydrophilic fabric has strong hydrophilic adsorption, resulting in sweat accumulation in the hydrophilic fabric and / or the laminated film layer, which cannot be discharged or diverted to the lower part of the clothes, causing discomfort when wearing. Summary of the invention
[0003] In response to the problems existing in the above-mentioned fabrics, the present invention makes further improvements to the hot melt adhesive used in the above-mentioned existing fabrics. The idea is to make the hot melt adhesive used for bonding waterproof fabrics and hydrophilic fabrics into a double-layer membrane structure with different elasticities, and form cracks in the membrane layer structure bonded to the waterproof fabric, so as to achieve sweat diversion through the cracks.
[0004] Based on the above concept, the fabric of the present invention needs to achieve the following objectives.
[0005] One of the goals is to achieve waterproof performance of 4 levels before washing, 3 levels after washing, and moisture permeability of 8000g / m 2 Above, water pressure resistance above 5000mmH2O, excellent UV blocking performance.
[0006] The second purpose is to achieve cracks in the composite adhesive layer of the double-layer membrane structure in the membrane layer that is bonded to the waterproof fabric.
[0007] The third purpose is that the peeling strength of the composite adhesive layer meets the wearing requirements.
[0008] Specifically, relevant performance, test methods and test indicators are shown in Table 1.
[0009] Table 1 Test items, test methods and test indicators
[0010]
[0011]
[0012] Using different elasticities of different film layers to form cracks in one of the film layers by stretching is a common method in the field of adhesive films. The key lies in selecting base films and crack films with different elasticities to achieve matching between the two. The core of the present invention is to explore a composite hot melt adhesive that can form cracks based on the hot melt adhesive disclosed in CN117757407A.
[0013] In the following tests, the waterproof fabric uses a waterproof nylon fabric with a yarn of 15D, and the hydrophilic fabric uses a hydrophilic floating yarn fabric with a yarn of 20D.
[0014] Test method: The molten first hot melt adhesive is coated on the hydrophilic fabric to form a first hot melt adhesive layer with a thickness of 10 μm; the molten second hot melt adhesive is coated on the molten first hot melt adhesive layer to form a second hot melt adhesive layer with a thickness of 15 μm; the waterproof fabric is bonded to the molten second hot melt adhesive layer to form a laminated fabric, and then the laminated fabric is stretched by 2% and cooled to form a test fabric. The peel strength of the obtained test fabric is tested to see if it meets the wearing requirements, and after separating the hydrophilic fabric and the waterproof fabric of the test fabric, observe whether the composite hot melt adhesive layer has cracks.
[0015] Test 1: Elastic matching test of different hot melt adhesives
[0016] In this experiment, the first hot melt adhesive is prepared by heating 75 parts of polyethylene glycol-based polyurethane elastomer and 13 parts of polyether polyol-modified silk fibroin to a molten state and mixing them evenly, and then adding 12 parts of nano-silicon dioxide and mixing them evenly; the polyether polyol-modified silk fibroin is prepared by esterifying silk fibroin and polyoxypropylene triol at a mass ratio of 1:1.2; the esterification reaction conditions are: catalyst thionyl chloride, pH=2-3, 45-50℃ reaction for 4h; the molecular weight of the silk fibroin is 800-1000, and the molecular weight of the polyoxypropylene triol is 3000-7000.
[0017] Test 1: The second hot melt adhesive layer uses polyethylene glycol-based polyurethane elastomer hot melt adhesive.
[0018] Test 2: The second hot melt adhesive layer uses low-density polyethylene (LDPE) hot melt adhesive.
[0019] Test 3: The second hot melt adhesive layer uses ethylene-vinyl acetate copolymer (EVA) hot melt adhesive.
[0020] Test 4: The second hot melt adhesive layer uses polyethersulfone resin (PES) hot melt adhesive.
[0021] Test 5: The second hot melt adhesive layer uses polyester amide (PEA) hot melt adhesive.
[0022] Test results: The peeling strength of the test fabrics of Tests 1 to 5 all met the wearing requirements, but each test fabric was elongated by 2%, and no cracks occurred in the first hot-melt adhesive layer and the second hot-melt adhesive layer.
[0023] Furthermore, the composite hot-melt adhesive layers of the test fabrics of Tests 1 to 5 were subjected to an ultimate tensile test, and the test results showed that the first hot-melt adhesive layer broke before the second hot-melt adhesive layer.
[0024] The above experimental / test results show that the second hot melt adhesive layer uses a single-component hot melt adhesive, which has better elasticity than the first hot melt adhesive layer. It is impossible to achieve cracks in only the second hot melt adhesive layer. Therefore, it is necessary to increase the elasticity of the first hot melt adhesive layer and / or reduce the elasticity of the second hot melt adhesive layer.
[0025] Test 2: Crack debugging test of composite hot melt adhesive
[0026] The elasticity of the hot melt adhesive layer is affected by factors such as fillers. Increasing the amount of fillers will reduce the elongation at break. The test results of Experiment 1 also show that the first hot melt adhesive layer contains 13 parts of polyether polyol-modified silk fibroin and 12 parts of nano-silica. Compared with the second hot melt adhesive layer of a single component polyethylene glycol-based polyurethane elastomer, its elongation at break is lower. It can be seen that polyether polyol-modified silk fibroin and nano-silica act as fillers. Therefore, under the premise of ensuring UV blocking performance, you can try to reduce the amount of polyether polyol-modified silk fibroin and / or nano-silica in the first hot melt adhesive, and increase polyether polyol-modified silk fibroin and / or nano-silica in the second hot melt adhesive. The specific test plan is as follows:
[0027] Test 6
[0028] The first hot melt adhesive: 70 parts of polyethylene glycol-based polyurethane elastomer and 25 parts of polyether polyol-modified silk fibroin.
[0029] The second hot melt adhesive: 50 parts of polyethylene glycol-based polyurethane elastomer, 20 parts of polyether polyol-modified silk fibroin, and 30 parts of nano-silicon dioxide.
[0030] Test 7
[0031] The first hot melt adhesive: 75 parts of polyethylene glycol-based polyurethane elastomer and 25 parts of polyether polyol-modified silk fibroin.
[0032] The second hot melt adhesive: 50 parts of low-density polyethylene (LDPE) hot melt adhesive, 20 parts of polyether polyol-modified silk fibroin, and 30 parts of nano-silicon dioxide.
[0033] Test 8
[0034] The first hot melt adhesive: 75 parts of polyethylene glycol-based polyurethane elastomer and 25 parts of polyether polyol-modified silk fibroin.
[0035] The second hot melt adhesive: 50 parts of ethylene-vinyl acetate copolymer (EVA) hot melt adhesive, 20 parts of polyether polyol-modified silk fibroin, and 30 parts of nano-silicon dioxide.
[0036] Test 9
[0037] The first hot melt adhesive: 75 parts of polyethylene glycol-based polyurethane elastomer and 25 parts of polyether polyol-modified silk fibroin.
[0038] The second hot melt adhesive: 50 parts of polyethersulfone resin (PES) hot melt adhesive, 20 parts of polyether polyol modified silk fibroin, and 30 parts of nano-silica.
[0039] Test 10
[0040] The first hot melt adhesive: 75 parts of polyethylene glycol-based polyurethane elastomer and 25 parts of polyether polyol-modified silk fibroin.
[0041] The second hot melt adhesive: 50 parts of polyester amide (PEA) hot melt adhesive, 20 parts of polyether polyol-modified silk fibroin, and 30 parts of nano-silica.
[0042] The above test method was used to carry out peel strength and crack tests on the test fabrics of Tests 6 to 10, and the results were as follows: the test fabrics of Tests 6 to 10 could not meet the required peel strength requirements; the hot melt adhesive layer of Tests 6, 7, and 8 only formed cracks in the second hot melt adhesive layer, and the hot melt adhesive layer of Tests 9 and 10 did not form cracks.
[0043] Test 3: Peel strength test of composite hot melt adhesive
[0044] According to previous research (CN117757407A), the peel strength of hot melt adhesive decreases with the increase of silicon dioxide content. In order to adjust the peel strength of composite hot melt adhesive, the following test was further conducted.
[0045] Test 11
[0046] The first hot melt adhesive: 75 parts of polyethylene glycol-based polyurethane elastomer and 25 parts of polyether polyol-modified silk fibroin.
[0047] The second hot melt adhesive: 60 parts of polyethylene glycol-based polyurethane elastomer, 20 parts of polyether polyol-modified silk fibroin, and 20 parts of nano-silicon dioxide.
[0048] Test 12
[0049] The first hot melt adhesive: 75 parts of polyethylene glycol-based polyurethane elastomer and 25 parts of polyether polyol-modified silk fibroin.
[0050] The second hot melt adhesive: 60 parts of low-density polyethylene (LDPE) hot melt adhesive, 20 parts of polyether polyol-modified silk fibroin, and 20 parts of nano-silica.
[0051] Test 13
[0052] The first hot melt adhesive: 75 parts of polyethylene glycol-based polyurethane elastomer and 25 parts of polyether polyol-modified silk fibroin.
[0053] The second hot melt adhesive: 60 parts of ethylene-vinyl acetate copolymer (EVA) hot melt adhesive, 20 parts of polyether polyol-modified silk fibroin, and 20 parts of nano-silica.
[0054] Test 14
[0055] The first hot melt adhesive: 75 parts of polyethylene glycol-based polyurethane elastomer and 25 parts of polyether polyol-modified silk fibroin.
[0056] The second hot melt adhesive: 20 parts of polyethylene glycol-based polyurethane elastomer, 20 parts of low-density polyethylene (LDPE) hot melt adhesive, 20 parts of ethylene-vinyl acetate copolymer (EVA) hot melt adhesive, 20 parts of polyether polyol-modified silk fibroin, and 20 parts of nano-silica.
[0057] Test 15
[0058] The first hot melt adhesive: 75 parts of polyethylene glycol-based polyurethane elastomer and 25 parts of polyether polyol-modified silk fibroin.
[0059] The second hot melt adhesive: 35 parts of polyethylene glycol-based polyurethane elastomer, 20 parts of low-density polyethylene (LDPE) hot melt adhesive, 15 parts of ethylene-vinyl acetate copolymer (EVA) hot melt adhesive, 10 parts of polyether polyol-modified silk fibroin, and 20 parts of nano-silica.
[0060] The above test method was used to carry out peel strength and crack tests on the test fabrics of Tests 11 to 15, and the results were as follows: the test fabrics of Tests 11 to 15 could all meet the required peel strength requirements, and the hot melt adhesive layers of the test fabrics of Tests 12 to 15 all formed cracks in the second hot melt adhesive layer; the test fabric of Test 11 did not form cracks in the second hot melt adhesive layer. The reason for this may be that the content of polyethylene glycol-based polyurethane elastomer in the second hot melt adhesive of Test 11 was similar to that in the first hot melt adhesive, resulting in little difference in elasticity between the second hot melt adhesive layer and the first hot melt adhesive layer, and no cracks could be formed.
[0061] Furthermore, the prepared test fabrics of Tests 12-15 were subjected to performance tests according to the test items and test methods shown in Table 1. The results are shown in Table 2.
[0062] Table 2 Test results of fabric performance in test examples 11-15
[0063]
[0064] It can be seen from the test results in Table 2 that the UV protection performance and heat shielding rate of the test fabrics of Tests 12 to 14 are not as good as those of the test fabric of Test 15, which means that when the second hot-melt adhesive layer does not contain polyethylene glycol-based polyurethane elastomer (Tests 12 and 13), or the content of polyethylene glycol-based polyurethane elastomer is low (Test 14), the UV protection performance and heat shielding rate of the obtained test fabrics are poor, and cannot meet the wearing requirements of the present invention; the test fabric of Test 15 can not only meet the various performance requirements of the wearing performance of the present invention, but also, relative to the composite hot-melt adhesives of Tests 12 to 14, can further reduce the amount of polyether polyol-modified silk fibroin in the second hot-melt adhesive layer, thereby reducing costs.
[0065] In combination with the above experiments and further research, the present invention is based on the existing hot melt adhesive for laminating anti-ultraviolet clothing fabrics, and optimizes the configuration of the hot melt adhesive so that the composite hot melt adhesive layer can form cracks in a single layer, thereby meeting the requirement that the sunscreen jacket can guide sweat. Specifically, it is achieved through the following technical solutions.
[0066] Provided is a composite fabric, including a waterproof fabric, a hydrophilic fabric, and a composite adhesive layer for bonding the waterproof fabric and the hydrophilic fabric; the composite adhesive layer includes a first hot melt adhesive layer and a second hot melt adhesive layer;
[0067] The first hot melt adhesive layer is formed by coating the first hot melt adhesive on the hydrophilic fabric by melting. The first hot melt adhesive is composed of the following raw material components per 100 parts by weight: 70-80 parts of thermoplastic polyurethane elastomer, 20-30 parts of polyether polyol-modified silk fibroin, and 0-5 parts of nano-silicon dioxide;
[0068] The second hot melt adhesive layer is formed by molten coating of the second hot melt adhesive on the first hot melt adhesive layer, and is used to bond the first hot melt adhesive layer and the hydrophilic fabric; the second hot melt adhesive is composed of the following raw material components per 100 parts by weight: 30-40 parts of thermoplastic polyurethane elastomer, 15-20 parts of ethylene-vinyl acetate copolymer, 15-25 parts of low-density polyethylene, 10-15 parts of polyether-polyol modified silk fibroin, and 20-25 parts of nano-silicon dioxide.
[0069] The polyether polyol-modified silk fibroin is prepared by esterification reaction of silk fibroin and polyether polyol; the esterification reaction conditions are: the mass ratio of silk fibroin to polyether polyol is 1:(1-1.5), the catalyst is thionyl chloride, the pH is 2-3, and the reaction time is 3-5h at 45-50°C; the polyether polyol is polyoxypropylene triol or polytetrahydrofuran diol.
[0070] Preferably, the molecular weight of the silk fibroin is 800-1000; the molecular weight of the polyoxypropylene triol is 3000-7000; and the molecular weight of the polytetrahydrofuran diol is 2000-3000.
[0071] The preparation method of the first hot melt adhesive is as follows: a thermoplastic polyurethane elastomer and a polyether polyol-modified silk fibroin are heated to 110-130° C. to a molten state and mixed evenly, and then nano-silicon dioxide is added and mixed evenly to obtain the first hot melt adhesive.
[0072] The preparation method of the second hot melt adhesive is as follows: thermoplastic polyurethane elastomer, ethylene-vinyl acetate copolymer, low-density polyethylene, and polyether polyol-modified silk fibroin are heated to 120-130° C. until they are molten and mixed evenly, and then nano-silicon dioxide is added and mixed evenly to obtain the second hot melt adhesive.
[0073] Preferably, the thermoplastic polyurethane elastomer is a polyether-type thermoplastic polyurethane elastomer or a polyester-type thermoplastic polyurethane elastomer, such as one of a polyethylene glycol-based polyurethane elastomer, a polyoxyethylene-based polyurethane elastomer, and a polytetrahydrofuran-based polyurethane elastomer.
[0074] Preferably, in the first hot melt adhesive, the nano-silicon dioxide is 2-5 parts.
[0075] Preferably, the thickness of the first hot melt adhesive layer is 5-10 μm.
[0076] Preferably, the thickness of the second hot melt adhesive layer is 10-15 μm.
[0077] Preferably, the waterproof fabric is a waterproof nylon fabric, and the hydrophilic fabric is a hydrophilic floating yarn fabric. More preferably, the yarn of the waterproof nylon fabric is 7D-20D; the yarn of the hydrophilic floating yarn fabric is 10D-30D.
[0078] The preparation method of the above-mentioned composite fabric includes the following steps: coating the molten first hot melt adhesive on the hydrophilic fabric to form a first hot melt adhesive layer; coating the molten second hot melt adhesive on the molten first hot melt adhesive layer to form a second hot melt adhesive layer; bonding the waterproof fabric to the molten second hot melt adhesive layer, and then cooling under stretching and 15-20°C environment.
[0079] Preferably, the elongation of the stretching is 1-2%.
[0080] Preferably, the cooling in the 15-20° C. environment is performed by air cooling, which is beneficial for the second hot melt adhesive layer to cool rapidly and form cracks.
[0081] In order to adapt to the automatic production of the composite fabric of the present invention, the composite fabric automatic production line used is as follows Figure 1As shown. The composite fabric automatic production line includes an unwinding roller 1, a first support roller 2, a winding roller 4, a cold air device 5, a second support roller 6, and a damping roller 7. The hydrophilic fabric and the waterproof fabric complete the first hot melt adhesive coating, the second hot melt adhesive coating, and the hydrophilic fabric and the waterproof fabric bonding process between the unwinding roller 1 and the first support roller 2. The bonded composite fabric 3 passes through the damping roller 7 and the second support roller 6 and is wound on the winding roller 4. A cold air device 5 is provided below the side close to the second support roller 6. The cold air device 5 is used to blow 15-20℃ cold air to the composite fabric 3 above. The damping roller 7 has a certain rotation resistance and is used to adjust the tension of the fabric between each process in the automatic production process, so as to achieve the adjustment of the elongation of the fabric in different processes; in the present invention, by setting the winding tension of the winding roller 4 and setting the damping roller 7, the elongation of the fabric between the winding roller 4 and the second support roller 6 is adjusted to 1-2%, and the elongation of the fabric between the unwinding roller 1 and the first support roller 2 is less than 1%. In some other embodiments, in order to adapt to the adjustment and control of the elongation, a plurality of damping rollers 7 ( Figure 1 There are three in the middle).
[0082] The present invention also provides a garment comprising the composite fabric.
[0083] In some specific embodiments, the above-mentioned clothing includes a spliced fabric formed by splicing a composite fabric and a hydrophilic fabric; the splicing is in a jagged shape.
[0084] The present invention adopts a double-layer composite hot melt adhesive. By improving the components of each layer of hot melt adhesive, the composite hot melt adhesive produces cracks on the side that is bonded to the waterproof fabric, while meeting the peeling strength requirements and maintaining excellent waterproof, moisture permeability, water pressure resistance, and ultraviolet light blocking properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0085] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for describing the embodiments are briefly introduced below.
[0086] Figure 1 It is a schematic diagram of the automatic production line of composite fabrics of the present invention.
[0087] Figure 2 This is a microstructure diagram of the second hot melt adhesive layer in the composite fabric of Example 2 of the present invention.
[0088] Figure 3 Schematic diagram of spliced fabrics on a jacket in Example 7 of the present invention.
[0089] Figure 4 Schematic diagram of splicing fabrics in Example 7 of the present invention. Description of the drawings:
[0091] 1-unwinding roller; 2-first supporting roller; 3-composite fabric; 4-winding roller; 5-cooling device; 6-second supporting roller; 7-damping roller; 8-spliced fabric; 81-composite fabric; 82-hydrophilic fabric. DETAILED DESCRIPTION
[0092] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0093] It should be further understood that the term "and / or" used in the present description and the appended claims refers to any and all possible combinations of one or more of the associated listed items, and includes these combinations.
[0094] The preparation method of the polyether polyol-modified silk fibroin used in the following examples / comparative examples is as follows.
[0095] Polyether polyol modified silk fibroin A: prepared by esterification reaction of silk fibroin and polyoxypropylene triol at a mass ratio of 1:1.2; the esterification reaction conditions are: catalyst thionyl chloride, pH=2-3, 45-50°C reaction for 4h; the molecular weight of the silk fibroin is 800-1000, and the molecular weight of the polyoxypropylene triol is 3000-7000.
[0096] Polyether polyol modified silk fibroin B: prepared by esterification reaction of silk fibroin and polyoxypropylene triol at a mass ratio of 1:1; the esterification reaction conditions are: catalyst thionyl chloride, pH = 2-3, 45-50°C reaction for 3h; the molecular weight of the silk fibroin is 800-1000; the molecular weight of the polyoxypropylene triol is 3000-7000.
[0097] Polyether polyol-modified silk fibroin C: The polyether polyol-modified silk fibroin is prepared by esterification of silk fibroin and polyoxypropylene triol at a mass ratio of 1:1.5; the esterification reaction conditions are: catalyst thionyl chloride, pH=2-3, 45-50°C for 5h; the molecular weight of the silk fibroin is 800-1000; the molecular weight of the polyoxypropylene triol is 3000-7000.
[0098] Polyether polyol-modified silk fibroin D: The polyether polyol-modified silk fibroin is prepared by esterification of silk fibroin and polytetrahydrofuran diol at a mass ratio of 1:1.3; the esterification reaction conditions are: catalyst thionyl chloride, pH=2-3, 45-50°C for 4h; the molecular weight of the silk fibroin is 800-1000; the molecular weight of the polytetrahydrofuran diol is 2000.
[0099] Polyether polyol-modified silk fibroin E: The polyether polyol-modified silk fibroin is prepared by esterification of silk fibroin and polytetrahydrofuran diol at a mass ratio of 1:1; the esterification reaction conditions are: catalyst thionyl chloride, pH=2-3, 45-50°C for 3h; the molecular weight of the silk fibroin is 800-1000; the molecular weight of the polytetrahydrofuran diol is 3000.
[0100] The preparation method of the composite fabric of the embodiment of the present invention is as follows:
[0101] 1) heating 70-80 parts of thermoplastic polyurethane elastomer and 20-30 parts of polyether polyol-modified silk fibroin to a molten state and mixing them evenly, and then adding 0-5 parts of nano-silicon dioxide and mixing them evenly to obtain a molten first hot melt adhesive; coating the molten first hot melt adhesive on the hydrophilic floating yarn fabric to form a first hot melt adhesive layer;
[0102] 2) heating 30-40 parts of thermoplastic polyurethane elastomer, 15-20 parts of ethylene-vinyl acetate copolymer, 15-25 parts of low-density polyethylene, and 10-15 parts of polyether polyol-modified silk fibroin until they are molten and mixed evenly, and then adding 20-25 parts of nano-silicon dioxide and mixing evenly to obtain a molten second hot melt adhesive; coating the molten second hot melt adhesive on the molten first hot melt adhesive layer to form a second hot melt adhesive layer;
[0103] 3) bonding the waterproof nylon fabric to the molten second hot melt adhesive layer, then stretching it to an elongation of 1-2%, and then cooling it with cold air at 15-20°C;
[0104] The yarn of the water nylon fabric is 7D-20D, the yarn of the hydrophilic floating yarn fabric is 10D-30D, the thickness of the first hot melt adhesive layer is 5-10μm, and the thickness of the second hot melt adhesive layer is 10-15μm. The thermoplastic polyurethane elastomer is one of polyethylene glycol-based polyurethane elastomer, polyoxyethylene polyurethane elastomer, and polytetrahydrofuran-based polyurethane elastomer.
[0105] Example 1
[0106] The preparation method of the composite fabric is as follows:
[0107] 1) heating 70 parts of polyethylene glycol-based polyurethane elastomer and 30 parts of polyether polyol-modified silk fibroin A to a molten state and mixing them evenly to obtain a molten first hot melt adhesive; coating the molten first hot melt adhesive on the hydrophilic floating yarn fabric to form a first hot melt adhesive layer;
[0108] 2) heating 40 parts of polyethylene glycol-based polyurethane elastomer, 15 parts of ethylene-vinyl acetate copolymer, 15 parts of low-density polyethylene, and 10 parts of polyether polyol-modified silk fibroin A to a molten state and mixing them evenly, and then adding 20 parts of nano-silicon dioxide and mixing them evenly to obtain a molten second hot melt adhesive; coating the molten second hot melt adhesive on the molten first hot melt adhesive layer to form a second hot melt adhesive layer;
[0109] 3) The waterproof nylon fabric is bonded to the molten second hot melt adhesive layer, then stretched to an elongation of 2%, and then cooled with cold air at 15°C.
[0110] The yarn of the waterproof nylon fabric is 10D; the thickness of the first hot-melt adhesive layer is 5μm, and the thickness of the second hot-melt adhesive layer is 15μm; the yarn of the hydrophilic floating yarn fabric is 20D.
[0111] Example 2
[0112] The preparation method of the composite fabric is as follows:
[0113] 1) heating 70 parts of polyethylene glycol-based polyurethane elastomer and 25 parts of polyether polyol-modified silk fibroin B to a molten state and mixing them evenly, and then adding 5 parts of nano-silicon dioxide and mixing them evenly to obtain a molten first hot melt adhesive; coating the molten first hot melt adhesive on the hydrophilic floating yarn fabric to form a first hot melt adhesive layer;
[0114] 2) heating 30 parts of polyethylene glycol-based polyurethane elastomer, 20 parts of ethylene-vinyl acetate copolymer, 15 parts of low-density polyethylene, and 10 parts of polyether polyol-modified silk fibroin B to a molten state and mixing them evenly, and then adding 25 parts of nano-silicon dioxide and mixing them evenly to obtain a molten second hot melt adhesive; coating the molten second hot melt adhesive on the molten first hot melt adhesive layer to form a second hot melt adhesive layer;
[0115] 3) bonding the waterproof nylon fabric to the molten second hot melt adhesive layer, then stretching it to an elongation of 1%, and then cooling it with cold air at 20°C;
[0116] The yarn of the water nylon fabric is 20D, the yarn of the hydrophilic floating yarn fabric is 10D, the thickness of the first hot melt adhesive layer is 10μm, and the thickness of the second hot melt adhesive layer is 10μm.
[0117] Example 3
[0118] The preparation method of the composite fabric is as follows:
[0119] 1) heating 80 parts of polyoxyethylene polyurethane elastomer and 20 parts of polyether polyol-modified silk fibroin C to a molten state and mixing them evenly to obtain a molten first hot melt adhesive; coating the molten first hot melt adhesive on the hydrophilic floating yarn fabric to form a first hot melt adhesive layer;
[0120] 2) heating 32 parts of polyoxyethylene polyurethane elastomer, 18 parts of ethylene-vinyl acetate copolymer, 14 parts of low-density polyethylene, and 14 parts of polyether polyol-modified silk fibroin C to a molten state and mixing them evenly, and then adding 22 parts of nano-silicon dioxide and mixing them evenly to obtain a molten second hot melt adhesive; coating the molten second hot melt adhesive on the molten first hot melt adhesive layer to form a second hot melt adhesive layer;
[0121] 3) bonding the waterproof nylon fabric to the molten second hot melt adhesive layer, then stretching it to an elongation of 1.5%, and then cooling it with cold air at 18°C;
[0122] The yarn of the water nylon fabric is 7D, the yarn of the hydrophilic floating yarn fabric is 30D, the thickness of the first hot melt adhesive layer is 5μm, and the thickness of the second hot melt adhesive layer is 13μm.
[0123] Example 4
[0124] The preparation method of the composite fabric is as follows:
[0125] 1) heating 72 parts of polyoxyethylene polyurethane elastomer and 25 parts of polyether polyol-modified silk fibroin D to a molten state and mixing them evenly, and then adding 3 parts of nano-silicon dioxide and mixing them evenly to obtain a molten first hot melt adhesive; coating the molten first hot melt adhesive on the hydrophilic floating yarn fabric to form a first hot melt adhesive layer;
[0126] 2) heating 35 parts of polyoxyethylene polyurethane elastomer, 15 parts of ethylene-vinyl acetate copolymer, 15 parts of low-density polyethylene, and 15 parts of polyether polyol-modified silk fibroin D to a molten state and mixing them evenly, and then adding 20 parts of nano-silicon dioxide and mixing them evenly to obtain a molten second hot melt adhesive; coating the molten second hot melt adhesive on the molten first hot melt adhesive layer to form a second hot melt adhesive layer;
[0127] 3) bonding the waterproof nylon fabric to the molten second hot melt adhesive layer, then stretching it to an elongation of 1.2%, and then cooling it with cold air at 20°C;
[0128] The yarn of the water nylon fabric is 12D, the yarn of the hydrophilic floating yarn fabric is 20D, the thickness of the first hot melt adhesive layer is 8μm, and the thickness of the second hot melt adhesive layer is 12μm.
[0129] Example 5
[0130] The preparation method of the composite fabric is as follows:
[0131] 1) heating 80 parts of polytetrahydrofuran-based polyurethane elastomer and 20 parts of polyether polyol-modified silk fibroin E to a molten state and mixing them evenly to obtain a molten first hot melt adhesive; coating the molten first hot melt adhesive on the hydrophilic floating yarn fabric to form a first hot melt adhesive layer;
[0132] 2) 30 parts of polytetrahydrofuran-based polyurethane elastomer, 15 parts of ethylene-vinyl acetate copolymer, 25 parts of low-density polyethylene, and 10 parts of polyether polyol-modified silk fibroin E are heated to a molten state and mixed evenly, and then 20 parts of nano-silicon dioxide are added and mixed evenly to obtain a molten second hot melt adhesive; the molten second hot melt adhesive is coated on the molten first hot melt adhesive layer to form a second hot melt adhesive layer;
[0133] 3) bonding the waterproof nylon fabric to the molten second hot melt adhesive layer, then stretching it to an elongation of 1.8%, and then cooling it with cold air at 15°C;
[0134] The yarn of the water nylon fabric is 15D, the yarn of the hydrophilic floating yarn fabric is 25D, the thickness of the first hot melt adhesive layer is 5μm, and the thickness of the second hot melt adhesive layer is 10μm.
[0135] Example 6
[0136] The preparation method of the composite fabric is as follows:
[0137] 1) heating 75 parts of polytetrahydrofuran-based polyurethane elastomer and 20 parts of polyether polyol-modified silk fibroin A to a molten state and mixing them evenly, and then adding 5 parts of nano-silicon dioxide and mixing them evenly to obtain a molten first hot melt adhesive; coating the molten first hot melt adhesive on the hydrophilic floating yarn fabric to form a first hot melt adhesive layer;
[0138] 2) 30 parts of polytetrahydrofuran-based polyurethane elastomer, 15 parts of ethylene-vinyl acetate copolymer, 15 parts of low-density polyethylene, and 15 parts of polyether polyol-modified silk fibroin A are heated to a molten state and mixed evenly, and then 25 parts of nano-silicon dioxide are added and mixed evenly to obtain a molten second hot melt adhesive; the molten second hot melt adhesive is coated on the molten first hot melt adhesive layer to form a second hot melt adhesive layer;
[0139] 3) bonding the waterproof nylon fabric to the molten second hot melt adhesive layer, then stretching it to an elongation of 2%, and then cooling it with cold air at 20°C;
[0140] The yarn of the water nylon fabric is 10D, the yarn of the hydrophilic floating yarn fabric is 15D, the thickness of the first hot melt adhesive layer is 8μm, and the thickness of the second hot melt adhesive layer is 15μm.
[0141] The fabrics prepared in Examples 1-6 were subjected to performance tests according to the test items and test methods shown in Table 1. The results are shown in Table 3.
[0142] Table 3 Fabric performance test results of Examples 1-6
[0143]
[0144] Example 2 The crack structure of the second hot melt adhesive layer in the composite fabric is as follows Figure 2shown.
[0145] During the research process of the present invention, the following comparative example verification was also carried out based on Example 2.
[0146] Comparative Example 1
[0147] The difference between the preparation method of the composite fabric of this comparative example and that of Example 2 is that the components of the first hot melt adhesive are: 70 parts of polyethylene glycol-based polyurethane elastomer, 20 parts of polyether polyol-modified silk fibroin B, and 10 parts of nano-silicon dioxide.
[0148] Comparative Example 2
[0149] The difference between the preparation method of the composite fabric of this comparative example and that of Example 2 is that the components of the first hot melt adhesive are: 65 parts of polyethylene glycol-based polyurethane elastomer, 25 parts of polyether polyol-modified silk fibroin B, and 10 parts of nano-silicon dioxide.
[0150] Comparative Example 3
[0151] The preparation method of the composite fabric in this comparative example is different from that in Example 2 in that the components of the second hot melt adhesive are: 30 parts of polyethylene glycol-based polyurethane elastomer, 15 parts of ethylene-vinyl acetate copolymer, 15 parts of low-density polyethylene, 10 parts of polyether polyol-modified silk fibroin B, and 30 parts of nano-silica.
[0152] Comparative Example 4
[0153] The preparation method of the composite fabric in this comparative example is different from that in Example 2 in that the components of the second hot melt adhesive are: 35 parts of polyethylene glycol-based polyurethane elastomer, 15 parts of ethylene-vinyl acetate copolymer, 15 parts of low-density polyethylene, 10 parts of polyether polyol-modified silk fibroin B, and 15 parts of nano-silica.
[0154] Comparative Example 5
[0155] The preparation method of the composite fabric in this comparative example is different from that in Example 2 in that the components of the second hot melt adhesive are: 20 parts of polyethylene glycol-based polyurethane elastomer, 20 parts of ethylene-vinyl acetate copolymer, 20 parts of low-density polyethylene, 10 parts of polyether polyol-modified silk fibroin B, and 25 parts of nano-silica.
[0156] Comparative Example 6
[0157] The preparation method of the composite fabric in this comparative example is different from that in Example 2 in that the components of the second hot melt adhesive are: 30 parts of polyethylene glycol-based polyurethane elastomer, 10 parts of ethylene-vinyl acetate copolymer, 15 parts of low-density polyethylene, 20 parts of polyether polyol-modified silk fibroin B, and 25 parts of nano-silica.
[0158] Comparative Example 7
[0159] The preparation method of the composite fabric in this comparative example is different from that in Example 2 in that the components of the second hot melt adhesive are: 40 parts of polyethylene glycol-based polyurethane elastomer, 15 parts of ethylene-vinyl acetate copolymer, 15 parts of low-density polyethylene, 5 parts of polyether polyol-modified silk fibroin B, and 25 parts of nano-silica.
[0160] Comparative Example 8
[0161] The difference between the preparation method of the composite fabric of this comparative example and that of Example 2 is that in step 3), the composite fabric is stretched to an elongation of 0.5%.
[0162] Comparative Example 9
[0163] The preparation method of the composite fabric of this comparative example is different from that of Example 2 in that, in step 3), the composite fabric is stretched to an elongation of 2.5%.
[0164] The fabrics prepared in Comparative Examples 1-9 were subjected to performance tests according to the test items and test methods shown in Table 1. The results are shown in Table 4.
[0165] Table 4 Comparative Examples 1-9 Fabric Performance Test Results
[0166]
[0167]
[0168] Example 7
[0169] A garment comprising the composite fabric of the present invention. Specifically, the garment is a jacket, and a spliced fabric 8 (such as Figure 3 As shown), the spliced fabric is formed by splicing the composite fabric 81 and the hydrophilic fabric 82 in a canine-tooth pattern (as shown Figure 4 As shown), the composite fabric 81 is located at the chest, and the hydrophilic fabric 82 is located at the waist and abdomen.
[0170] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can easily think of various equivalent modifications or replacements within the technical scope disclosed by the present invention, and these modifications or replacements should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be based on the protection scope of the claims.
Claims
1. A composite fabric, characterized in that: It includes a waterproof fabric, a hydrophilic fabric, and a composite adhesive layer for bonding the waterproof fabric and the hydrophilic fabric; the composite adhesive layer includes a first hot melt adhesive layer and a second hot melt adhesive layer; The first hot melt adhesive layer is formed by coating the first hot melt adhesive on the hydrophilic fabric by melting. The first hot melt adhesive is composed of the following raw material components per 100 parts by weight: 70-80 parts of thermoplastic polyurethane elastomer, 20-30 parts of polyether polyol-modified silk fibroin, and 0-5 parts of nano-silicon dioxide; The second hot melt adhesive layer is formed by molten coating of the second hot melt adhesive on the first hot melt adhesive layer, and is used to bond the first hot melt adhesive layer and the hydrophilic fabric; the second hot melt adhesive is composed of the following raw material components per 100 parts by weight: 30-40 parts of thermoplastic polyurethane elastomer, 15-20 parts of ethylene-vinyl acetate copolymer, 15-25 parts of low-density polyethylene, 10-15 parts of polyether-polyol modified silk fibroin, and 20-25 parts of nano-silicon dioxide.
2. The composite fabric according to claim 1, characterized in that: The polyether polyol-modified silk fibroin is prepared by esterification reaction of silk fibroin and polyether polyol; the esterification reaction conditions are: the mass ratio of silk fibroin to polyether polyol is 1:(1-1.5), the catalyst is thionyl chloride, the pH is 2-3, and the reaction time is 3-5h at 45-50°C; the polyether polyol is polyoxypropylene triol or polytetrahydrofuran diol.
3. The composite fabric according to claim 1, characterized in that: The thermoplastic polyurethane elastomer is a polyether type thermoplastic polyurethane elastomer or a polyester type thermoplastic polyurethane elastomer.
4. The composite fabric according to claim 1, characterized in that: In the first hot melt adhesive, the nano silicon dioxide is 2-5 parts.
5. The composite fabric according to claim 1, characterized in that: The thickness of the first hot melt adhesive layer is 5-10 μm.
6. The composite fabric according to claim 5, characterized in that: The thickness of the second hot melt adhesive layer is 10-15 μm.
7. The method for preparing the composite fabric according to any one of claims 1 to 6, characterized in that: The following steps are involved: The molten first hot melt adhesive is coated on the hydrophilic fabric to form a first hot melt adhesive layer; the molten second hot melt adhesive is coated on the molten first hot melt adhesive layer to form a second hot melt adhesive layer; the waterproof fabric is bonded to the molten second hot melt adhesive layer, and then cooled under stretching and 15-20°C environment.
8. The preparation method according to claim 7, characterized in that: The elongation of the stretching is 1-2%.
9. A kind of clothing, characterized in that: The composite fabric comprises the composite fabric as described in any one of claims 1 to 8.
10. The clothing according to claim 9, characterized in that: The invention relates to a spliced fabric formed by splicing a composite fabric and a hydrophilic fabric; the splicing is in a jagged shape.
Citation Information
Patent Citations
Hot-melt adhesive tape and preparation method thereof
CN105969226A
Cloth capable of being automatically adjusted according to humidity change, preparation process and clothes
CN112918058A
Hot melt adhesive for laminating anti-ultraviolet garment fabric as well as preparation method and application of hot melt adhesive
CN117757407A
Heat adhesive membrane structure having a moist permeable and water proof properties and manufacturing method thereof
KR102263969B1